On Principally Generalized Lifting Modules - Hassan, Aseel Amer (Al-Nahrain Journal of Science, 2017)
In this paper we introduce principally generalized lifting as a generalization of principally lifting modules and we prove under certain conditions some relations between Mj-projective (quasidiscrete) and PGD1.